Evaluation of the Aptima HCV Quant Dx Assay for Hepatitis C Virus RNA Detection from Fingerstick Capillary Dried Blood Spot and Venepuncture-Collected Samples. (25th July 2020) - Catlett, Beth; Bajis, Sahar; Starr, Mitchell; Dore, Gregory J; Hajarizadeh, Behzad; Cunningham, Philip H; Applegate, Tanya L; Grebely, Jason
Abstract: Background: Simplified diagnostic strategies are needed increase hepatitis C virus (HCV) testing to determine active infection and link people into treatment. Collection methods such as dried blood spots (DBS) have advantages over standard phlebotomy, especially within marginalized populations. Methods: We evaluated the diagnostic performance of the Aptima HCV Quant assay for the quantification and detection of HCV RNA from paired DBS and venepuncture samples. Specimens were collected from participants enrolled in an Australian observational study. We compared HCV RNA detection from DBS against venepuncture samples (gold standard). Results: One hundred sixty-four participants had paired samples and HCV RNA was detected in 45 (27% [95% confidence interval, 21%–35%]) by the Aptima assay in venepuncture samples. Sensitivity of the Aptima assay for HCV RNA quantification from DBS (≥10 IU/mL in plasma) was 100% and specificity was 100%. Sensitivity for HCV RNA detection from DBS was 95.6% and specificity was 94.1%. A small bias in plasma over DBS was observed with good agreement ( R 2 = 0.96). Conclusions: The Aptima HCV Quant assay detects active infection from DBS samples with acceptable diagnostic performance and is clinically comparable to plasma. These data will strengthen the case for the registration of a DBS kit insert claim, enabling future clinical utility. Abstract : The Aptima HCV Quant assay detects active infection from capillary-fingerstick collected dried blood spots with acceptable diagnostic performance and is clinically comparable to plasma.